PENGARUH KUALITAS PELAYANAN KARYAWAN TERHADAP KEPUASAN KONSUMEN DI CFC BASKO GRAND MALL PADANG - Fajri, Yaumil; Yuliana, Yuliana; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research arouse from the experience of researcher when visiting the CFC Basko Grand Mall Padang, that the consumers dissatisfaction with the quality of service of the employees in serving consumers. This reseach aims to see how much the influence of the variable of Quality Service (X) toward Consumer Satisfaction (Y) at the CFC Basko Grand Mall Padang. The sample in this research amounted to 100 people taken using the technique Purposive sampling technique. Data collection is done by questionnaire by using Likert scale that has been tested of the validity and reliability. The results indicate that: (1) Quality of Service is in the category of less agree (61%), (2) Consumer Satisfaction is in the less satisfied category (58%), (3) Result of simple linear regression hypothesis test obtained R Square equal to 0,309 , It means that service quality influence consumer satisfaction 30,9%, and 69,1% influenced by other factors likes: product quality, price, situation, and personal factor of consumer. Furthermore, the value obtained by regression coefficient of 0.322. This means that every increase of 1 unit of service quality will increase 0.322 units of customer satisfaction.